Authentication scheme of smart home based on eUICC - Yan LI; Yanqing LU; Rong ZHANG; Maowen GUO (Dianxin kexue)
The main existing security risks in smart home services was analyzed.For the reason of these risks,the key points of smart home security and also the authentication scheme based on eUICC were put forward,including the overall architecture,main module interactions,key processes,etc.Finally,the application of eUICC in the field of smart home was prospected.